Pengaruh Kinerja Pengelola Keuangan dan Pemanfaatan Teknologi Informasi terhadap Kualitas Pelaporan Keuangan - Jonathan Setiadi; Florencia Irena Lawita (UNIVERSITAS KALBIS, 2026)
This study aims to examine the effect of financial manager performance and the utilization of information technology on the quality of financial reporting in PT Indotruck. The quality of financial reporting is one of the important indicators in the transparency and accountability of financial management. This study uses a quantitative approach with a survey design. The data analysis method used is multiple linear regression to test the effect of financial manager performance variables and the utilization of information technology on the quality of financial reporting. The results of the study indicate that financial manager performance and the utilization of information technology have a significant effect on the quality of financial reporting. The utilization of information technology, especially in the form of accounting software, has been shown to increase the accuracy and efficiency of financial reporting. This study provides implications for financial managers and organizations to further improve the competence of financial managers and maximize the utilization of information technology to produce quality financial reports.